REFRAMING THE PROPHET’S INTERACTIONS WITH NON MUSLIMS: A CONTEXT-SENSITIVE MODEL OF RELIGIOUS MODERATION FROM THE SĪRAH NABAWIYYAH - Nasrulloh, Muhammad; Zakky Ubaid Ermawan, Mohamad; Anam, Khoirul; Thoriquddin, Moh. (Harmoni, 2025)
This study examines the Prophet Muhammad’s interactions with non‑Muslims in the Sīrah Nabawiyyah to construct a context-sensitive model of religious moderation applicable to contemporary plural societies. Existing research often highlights his tolerance but rarely provides a systematic classification of his interactions across diverse social and political settings, leaving a gap in developing an operational framework for religious moderation. This study employs qualitative library research using primary hadith data supported by classical and contemporary exegetical and historical sources. The data were analyzed through descriptive, comparative, and contextual interpretation to map patterns of interaction in Mecca and Medina. The findings show, first, that Muhammad’s moderation was shaped by context: defensive in Mecca under persecution and protective in Medina as a political leader. Second, his interactions with non‑Muslims fall into distinct categories—adversaries, allies, captives, and family members—each demonstrating different ethical responses ranging from firmness toward hostile groups to justice and compassion toward peaceful communities. Third, five dimensions of moderation emerge: protection in social authority, justice in law enforcement, synergy in socio-economic relations, empathy in social and environmental engagement, and freedom in religious practice. These findings offer an empirically grounded framework for strengthening interfaith harmony, informing policy, and enhancing religious education. The study concludes that moderation in Islam is dynamic and adaptable, providing practical guidance for managing diversity in modern societies.  Abstrak Penelitian ini menelaah interaksi Nabi Muhammad dengan non‑Muslim dalam Sīrah Nabawiyyah untuk membangun model moderasi beragama yang peka konteks dan relevan bagi masyarakat plural kontemporer. Penelitian sebelumnya sering menyoroti sikap toleransi beliau, tetapi jarang menyediakan klasifikasi sistematis atas interaksi beliau dalam berbagai setting sosial dan politik, sehingga menyisakan kesenjangan dalam pengembangan kerangka moderasi beragama yang operasional. Penelitian ini menggunakan metode kualitatif berbasis studi pustaka dengan data primer berupa hadis, didukung sumber tafsir dan sejarah klasik maupun kontemporer. Data dianalisis melalui pendekatan deskriptif, komparatif, dan interpretasi kontekstual untuk memetakan pola interaksi di Makkah dan Madinah. Temuan penelitian ini menunjukkan, pertama, bahwa moderasi Muhammad dibentuk oleh konteks: bersifat defensif di Makkah ketika mengalami penindasan dan protektif di Madinah ketika memimpin komunitas politik. Kedua, interaksi beliau dengan non‑Muslim terbagi dalam beberapa kategori: musuh, sekutu, tawanan, dan anggota keluarga, yang masing‑masing menampilkan respons etis berbeda, mulai dari ketegasan terhadap kelompok bermusuhan hingga keadilan dan kasih sayang terhadap komunitas yang damai. Ketiga, muncul lima dimensi moderasi: perlindungan dalam otoritas sosial, keadilan dalam penegakan hukum, sinergi dalam hubungan sosial‑ekonomi, empati dalam relasi sosial dan lingkungan, serta kebebasan dalam praktik keagamaan. Temuan ini menawarkan kerangka empiris untuk memperkuat harmoni antaragama, mendukung perumusan kebijakan, dan meningkatkan pendidikan keagamaan. Studi ini menyimpulkan bahwa moderasi dalam Islam bersifat dinamis dan adaptif, serta memberikan panduan praktis dalam mengelola keberagaman di masyarakat modern